2017
DOI: 10.17503/agrivita.v39i1.895
|View full text |Cite
|
Sign up to set email alerts
|

Embryogenic Callus Induction from Leaf Tip Explants and Protocorm-Like Body Formation and Shoot Proliferation of Dimorphorchis lowii: Borneon Endemic Orchid

Abstract: Dimorphorchis lowii is a rare epiphytic orchid endemic to Borneo and very popular due to its ornamental value. For the purpose of mass propagation, procedures for in vitro propagation through callus were developed. The objectives of this study were to determine the effects of plant growth regulators (PGRs) on callus induction from leaf tip explant and the effects of complex additives on PLBs formation and shoot development. The best combination of PGR was 3.0 mg L -1 Thidiazuron (TDZ) with 0.046 mg L -1 NAA su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(35 reference statements)
3
6
0
2
Order By: Relevance
“…In the sixth week, the leaf callus cultures showed the presence of embryo-like cells which vary in their shape and morphology (Figure 4C). Similar observations were also reported by Jainol & Gansau (2017) in Dimorphorchis lowii. In the subsequent sub-cultures, the callus developed globular, torpedo, cordite and elongated shaped embryoids (Figure 4D, E, F, and G).…”
Section: Sem Analysissupporting
confidence: 91%
“…In the sixth week, the leaf callus cultures showed the presence of embryo-like cells which vary in their shape and morphology (Figure 4C). Similar observations were also reported by Jainol & Gansau (2017) in Dimorphorchis lowii. In the subsequent sub-cultures, the callus developed globular, torpedo, cordite and elongated shaped embryoids (Figure 4D, E, F, and G).…”
Section: Sem Analysissupporting
confidence: 91%
“…This suggested that transformant plants formed a much higher number of shoots per plant than that of nontransformant plants. This phenomenon is similar to that shown by Jainol & Gansau (2017), that because of the activity of the transgene AtRKD4, every cell in protocorm can undergo a change of self-identity, there is dedifferentiation occurred to form somatic embryos, and each embryo then grows into shoot. The high production of shoots in orchid transformant was consistent to the result of ectopic expression of AtRKD4 in Arabidopsis (Chardin, Girin, Roudier, Meyer, & Krapp, 2014), that causes some plant growth distortions including abnormal tissue proliferation.…”
Section: Phenotypic Analysis Of 8 Months Regenerated Transformant Plantssupporting
confidence: 81%
“…It is promising that the in vitro cultivation (micropropagation) utilizing somatic embryogenesis process can produce plantlets that morphologically and genetically uniform. Meanwhile, Jainol & Gansau (2017) got the highest percentage (96 %) of protocorm like bodies (PLB) from leaf tip explants of Borneon endemic orchid, Dimorphorchis lowii is cultured on Murashige and Skoog medium supplemented with Thidiazuron and Naphtalene acetic acid. PLB is special term for somatic embryo in orchids and somatic embryogenesis is the process of embryo formation derived from somatic cells (Lee, Hsu, & Yeung, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetative propagation is commonly used by cutting of shoot. Generative propagation by using seed has low success rate, because the orchid seed have no endosperm (Jainol & Gansau, 2017). Conventional method through seed propagation is sometimes problematic as seed germination in natural environment is a slow process and it requires mycorrhizal or fungal contribution (Parthibhan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%